Exploring the future of nursing: Insights from the ChatGPT model - Joko Gunawan (Belitung Nursing Journal, 2023)
This editorial aims to provide a comprehensive overview of the future of nursing through the lens of the ChatGPT model, a state-of-the-art language processing artificial intelligence (AI) developed by OpenAI. The edited chat transcripts with ChatGPT may offer key trends and developments in nursing, such as the increasing use of technology and digital tools, the integration of AI, and the use of robotics in patient care, as well as insights into the implications of these changes for nurses, patients, and the healthcare system as a whole. However, the future of nursing is continuously evolving. Therefore, nurses need to keep abreast of the latest developments and adapt to them while remaining committed to providing quality care.